A content validity of freediving recreation (Without fins) training to improve psychological conditions and physical health - Solikhin, Muhamad Nanang; Sumaryanti, Sumaryanti; Sulistiyono, Sulistiyono; Fauzi, Fauzi; Arbanto, Bonifacius (Studia sportiva, 2024)
The aim of this research is to construct a theoretical concept, theme “Recreational Freediving Program without fins” for beginners, which will be used to improve psychological conditions vital and lung capacity through an 8-week training program. The research participants were Yogyakarta State University students who were over 18 years old and had anxiety disorders as measured using the DASS-21 instrument. The reason for choosing a recreational freediving training program that does not use fins is because it is cost-effective and easy to do. Also, consider the recommended freediving training principles This research uses mixed methods. This study combines two approaches, namely qualitative and quantitative. The seven experts' participation was determined by criteria of freediving, Sport aquatic expert, sport coaching expert and phycological expert. The qualitative stage for data collection uses the Delphi technique. This research was conducted with content validity with Aiken's V index. Based on the research Aiken's analysis results compared with the value of the V table in the evaluation using 7 expert judgments with 5 alternative scales at a significance and level of 5% is V Score (0.79 to 0.89) > V table 0,75, it mean the freediving recreational exercise program with no fins that conduct to increase phycological condition and lung capacity is valid. This finding underscores some of the essential skills that are necessary for a successful and safe freediving experience for beginners who have anxiety.